Analysis of The Use of Facebook Digital Promotion Media To Increase Sales of UD Tahu Murni Products in Gunungsitoli City - Petrus Lase; Idarni Harefa; Yupiter Mendrofa; Otanius Laia (Economics and Business Journal (ECBIS), 2025)
This study aims to determine how social media is utilized Facebookas a digital promotional tool at UD. Tahu Murni in Gunungsitoli City, and to identify factors that hinder the effectiveness of such promotions in increasing sales. The background of this study is the increasingly rapid development of information technology that encourages micro, small, and medium enterprises (MSMEs) to utilize digital media as a more efficient promotional strategy and reach a wider market. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of business owners and several consumers. The data obtained were analyzed using thematic analysis methods. The results of the study indicate that the use of Facebook as a promotional medium by UD. Tahu Murni has not been optimally implemented. The promotional content uploaded is still simple, inconsistent, and has not utilized strategic features such as paid advertising (Facebook Ads), customer interaction, and social media analytics. The main inhibiting factors in optimizing promotions through Facebook are the business owner's limited digital knowledge, limited time, and the lack of a workforce focused on digital marketing. This study recommends that business actors improve their understanding and skills in social media management, utilize digital promotional features optimally, and develop attractive and consistent content strategies to reach more consumers.